Al-munÄáº“arah Al-â€˜Ilmiyyah bi Al-Lugati Al-â€˜Arabiyyati Aá¹¡nÄâ€™ IntisyÄr KaufÄ«d-19: Hal Hiya Mumkinah? - Maturedy, Faris; Wargadinata, Wildana; Maimunah, Iffat (Departemen Pendidikan Bahasa Arab, 2021)
The Arabic debate competition was canceled due to the Covid 19 pandemic. So that ITHLA held the competition through zoom. Meanwhile, the Arabic Language Education Study Program held an Arabic language debate through WhatsApp. The researcher aims to describe the Arabic debate amid the Covid 19 pandemic. Researchers used a qualitative approach. Researchers obtained data by observation, interviews, and documentation. Meanwhile, the data were analyzed descriptively. The result of this research is that debates during the pandemic are carried out through zoom and WhatsApp. The challenge is that this activity can be followed by Arabic language students throughout Indonesia because the Arabic debate is only followed by students in Java. Meanwhile, the problem is that students have to make sure their signal is good. Also, debates via WhatsApp at IAIN Jember lowered student interest. Meanwhile, students who debated through zoom found difficulties in rebutting.